Ai Feeder / Nur Hazni Mohamad Rodzi - Mohamad Rodzi, Nur Hazni (2020)
Pet care should be fun, not burdensome, and so the goal of this project is to assist owner with pet care by providing an automatic pet feeder. The purpose of the project helps the owner of the pet feeding their pet on time even when they are not at home. Nowadays, people want to have pet as their companion buddies or add value to the family. However, due to busy lifestyle and must travel and leaving the pet make pet parent minimize their mobilities. Other than that, it also can help the owner know the diet of their pet. Knowing the diet of the pet is very important for the owner to make sure that the pet is in good health. This system assists pet owner to feed the pet. Ai Feeder is using high technology by using current technology which is RFID tag. Ai feeder have potential to be positioned as one of the successful automatic pet feeder business throughout the country with our creative innovation. Our overview for this industry is complex and fast growing due to the advance of technology. Our product is open to all people especially family and pet lover. This Ai feeder has function and advantages not found in today’s common pet feeder thus providing a competitive advantage over more established competitors.